A facile approach to realize simultaneously chain extension and crystallization promotion of poly (ethylene terephthalate). (August 2021) - Huang, Wei-Tao; He, Guang-Jian; Tang, Wen-Dong; Zou, Xin-Liang; Yin, Xiao-Chun
Highlights: Chain extension and crystallization promotion of PET are realized simultaneously. Chemical nucleation couldn't impair chain extension effect. Low content of Na-LL could significantly promote crystallization of PET. This strategy could maintain excellent mechanical properties of PET. Abstract: A synergic strategy combining chemical nucleation with chain extension was employed for Poly (ethylene terephthalate) (PET). In this study, sodium linoleate (Na-LL), as chemical nucleating agent, was selected to promote the nucleation process, and an ultraviolet-induced chain extension approach was simultaneously employed to maintain the molecular weight of PET with the aid of glycidyl methacrylate (GMA) / trimethylolpropane triacrylate (TMPTA). The rheological properties, crystallization behaviors and mechanical properties of PET composites were systematically explored. The rheological results showed that GMA/TMPTA blend is effective for PET chain extension reaction and the addition of Na-LL would not badly offset the chain extension effect of GMA/TMPTA. The non-isothermal and isothermal crystallization studies demonstrated that Na-LL is an effective organic nucleating agent for PET. Low loading of Na-LL can considerably improve the crystallization properties of PET. At last, the combination of GMA/TMPTA/Na-LL could also maintain the excellent comprehensive mechanical properties of PET. Graphical abstract: Sodium linoleate (Na-LL) acted as chemical nucleating agent for PET, which was employed to improve its crystallization properties. Meanwhile, with the assistance of glycidyl methacrylate (GMA) / trimethylolpropane triacrylate (TMPTA), an ultra-violet induced chain extension of PET was employed to compensate for the degradation caused by Na-LL and maintain its excellent mechanical properties. Through this simple method, the crystallization promotion and chain extension of PET can be reached simultaneously. Image, graphical abstract